Homo Promptus : Predicting the impact of generative AI on human memory and creativity - Linden, Katerina; Hachem, Hugo Henrik; Kondyli, Vasiliki (Memory, Mind and Media, 2025)
This article explores the transformational potential of artificial intelligence (AI), particularly generative AI (genAI) - large language models (LLMs), chatbots, and AI-driven smart assistants yet to emerge - to reshape human cognition, memory, and creativity. First, the paper investigates the potential of genAI tools to enable a new form of human-computer co-remembering, based on prompting rather than traditional recollection. Second, it examines the individual, cultural, and social implications of co-creating with genAI for human creativity. These phenomena are explored through the concept of Homo Promptus, a figure whose cognitive processes are shaped by engagement with AI. Two speculative scenarios illustrate these dynamics. The first, 'prompting to remember', analyses genAI tools as cognitive extensions that offload memory work to machines. The second scenario, 'prompting to create', explores changes in creativity when performing together with genAI tools as co-creators. By mobilising concepts from cognitive psychology, media and memory studies, together with Huizinga's exploration of play, and Rancière's intellectual emancipation, this study argues that genAI tools are not only reshaping how humans remember and create but also redefining cultural and social norms. It concludes by calling for 'critical' engagement with the societal and intellectual implications of AI, advocating for research that fosters adaptive and independent (meta)cognitive practices to reconcile digital innovation with human agency.
Publisher Copyright: © The Author(s), 2025. Published by Cambridge University Press.
Keywords: collective memory; creativity; generative AI; Homo Ludens; mnemonic prosthetics; prompting; third way of memory